A prospective randomized comparison of primary outcome between laparoscopic appendectomy and open appendectomy - T, Shivakumar; Ranjan, Ved Prakash; V. S., Yamuna; P., Karthik (International Surgery Journal, 2017)
Background: Open appendectomy is one of the most common surgeries done in an emergency operation theatre even after three decades of introduction of laparoscopic surgeries. The previous studies done on laparoscopic appendectomy produced conflicting recommendations, and the adequacy of sample sizes is generally unknown. We compared primary outcomes after laparoscopic and open appendectomy in a sample of predetermined statistical power. Methods: A pre-study power analysis suggested that 200 randomized patients would yield 80% power to show a mean decrease of 1.3 days hospitalization. One hundred ninety-eight patients with a preoperative diagnosis of acute appendicitis were randomized prospectively to laparoscopic or open appendectomy. The primary outcomes measured were duration of operative time, postoperative pain and analgesia, length of hospital stay and cosmetic advantages. Results: It was found that mean operation time was 33±5.8 minute and 37± 7.5 minute in OA and LA respectively. Duration of post-operative hospital stay was 1.2 days shorter in Laparoscopic group. LA required 1.1 shots of less analgesic than OA. Oral feeding was resumed 21 hours earlier following LA compared to OA. Laparoscpic appendectomy was safely performed in paediatric patient without any adverse effect. We also found that, in female patient, concurrent ovarian cysts, tubal pregnancy and endometriosis can be diagnosed and managed laparoscopically in the same sitting. Conclusions: Present study found that laparoscopic appendectomy is an effective and safe procedure irrespective of age and sex of the patient. LA has added advantage of early return of bowel movement, less post-op hospital stays and less requirement of narcotic analgesic.